Pengaruh Persepsi Biaya Brand Image Dan Promosi Terhadap Keputusan Mendaftar Kuliah di Politeknik LP3I - Ahyar, Nurul (POLITEKNIK LP3I, 2024)
Higher education plays a strategic role in preparing human resources competent in the industrial world. Politeknik LP3I, as a vocational education institution, faces challenges in attracting prospective students amidst increasingly tight competition. This study aims to analyze the influence of cost perception, brand image, and promotion on prospective students' decisions to enroll at Politeknik LP3I. The research method used is descriptive qualitative research with a literature review, utilizing articles, journals, theses, and other related studies. The data used in this study is secondary data, obtained through documentation of literature studies. The findings indicate that cost perception, brand image, and promotion significantly affect prospective students' decisions to enroll at Politeknik LP3I. Affordable cost perceptions, positive brand image, and effective promotion increase prospective students' interest in choosing Politeknik LP3I for higher education. This study provides valuable insights for the management of Politeknik LP3I to formulate more effective marketing strategies.